The Effects of Mexico-U.S. Migration on the Intergenerational Educational Mobility of Youth in Mexico - Sanchez-Soto, Gabriela (Papeles de Población; Vol. 23 Núm. 93 (2017): Papeles de Población, 2018)
This paper studies the role of U.S. migration on the intergenerational educational mobility of non-migrant youth in Mexico by using data from the 10% sample of the 2010 Mexican Census to compare the educational attainment of youth ages 13 to 20 to their parents’ attainment. Classic models of status attainment suggest family background is a strong determinant of youth’s educational outcomes. U.S. migration in the household is expected to positively influence education through its positive impact on socioeconomic status. However, previous research has not explored the role of the place of residence on the educational outcomes of youth relative to their parents. Living in a place with high U.S. migration prevalence has been associated with schooling discontinuation and an orientation towards U.S. labor markets. Results show migration at the household level has distinct effects from community level migration. While migrants in the household and receipt of remittances are related to higher odds of upward intergenerational mobility, higher migration prevalence in the community is associated with lower probabilities of upward intergenerational educational mobility. Also, results show the effects of migration in the household depend on the socioeconomic conditions of the community of residence. Household migration effects are stronger in less developed areas. These findings have important implications for our understanding of the long-term educational impacts of migration on non-migrant youth, and to influence the development of conceptual frameworks to understand the impacts of migration in the household and the community.